White light-emitting contrast image capsule endoscopy for visualization of small intestine lesions: a pilot study - Ogata, Noriyuki; Ohtsuka, Kazuo; Sasanuma, Seiko; Ogawa, Masataka; Maeda, Yasuharu; Ichimasa, Katsuro; Mori, Yuichi; Misawa, Masashi; Kudo, Toyoki; Hisayuki, Tomokazu; Hayashi, Takemasa; Wakamura, Kunihiko; Miyachi, Hideyuki; Baba, Toshiyuki; Ishida, Fumio; Kudo, Shin-ei (Endoscopy International Open, 2018)
Background and study aims Capsule endoscopy (CE) has become a routine means of diagnosing obscure gastrointestinal bleeding (OGIB) in the small intestine. Capsules using novel blue-enhanced white light-emitting diodes are expected to acquire clearer contrast images (CIs) of the small bowel vasculature. We conducted a pilot study to examine whether CIs facilitate visualization of small bowel erosions, ulcers, and areas of angioectasia compared with standard white light images (WLIs).Patients and methods A total of 24 patients with OGIB were recruited in this study. The main outcome measure was visibility of lesions on CIs compared with WLIs. We also examined the color difference between lesions and normal mucosa (ΔE) with each imaging modality.Results Three experienced physicians retrospectively evaluated 138 images of small bowel lesions (107 erosions, or ulcers, and 31 areas of angioectasia) obtained from 24 CE examinations. The endoscopists judged that compared with WLIs, CIs afforded easier identification of erosions or ulcers in 29 of 107 cases (27.1 %), were non-inferior in 68 of 107 cases (63.6 %), and were inferior in 10 of 107 cases (9.3 %). Identification of angioectasia was judged to be easier with CIs in 15 of 31 cases (48.4 %), non-inferior in 13 of 31 cases (41.9 %), and inferior in 3 of 31 cases (9.7 %). ΔE was significantly higher for CIs than WLIs, especially for angioectasia, potentially explaining why lesions were easier to visualize.Conclusions CIs obtained by CE appear to facilitate identification of small bowel erosions, ulcers, and areas of angioectasia compared with WLIs.